The Role of Leadership in Decision Making - Harahap, Rahmaya Sari; Syahputra, Dwi Cahyo; Sinaga, Sariani Eva Agustina (Jurnal Riset Ilmu Pendidikan, 2023)
The purpose of this study is to investigate how leadership functions in decision-making. This study uses a literature-based method with a qualitative approach. Information was collected from a number of relevant journals. After the data collection process, content analysis techniques were used to analyze the data through a text analysis approach. The results of the study indicate that leadership plays a significant role in the decision-making process. Some leadership roles in this context include as a person (personal), educator (educator), manager (manager), administrator, supervisor, leader, creator of a conducive work climate, innovator, and motivator. It can be concluded that a leader acts as a problem solver, negotiator, and resource allocation manager in their capacity as a decision-maker. This role requires leaders to be able to consider various strategic aspects in every policy taken, especially in the field of education. These considerations emphasize that leaders have a moral and professional responsibility to act in the best interests of the educational organization, by upholding continuity, integrity, and accountability in every decision made.